HEPATIC HISTOPATHOLOGY OF WHITE RATS EXPOSED TO LEAD AND TREATED WITH MORINGA OLEIFERA LEAF SIMPLICIA - Paula Bintang Wuriandari; I Ketut Berata; Ida Bagus Oka Winaya; I Made Kardena; Ni Luh Eka Setiasih; Samsuri; Ni Nyoman Werdi Susari (Buletin Veteriner Udayana, 2026)
Lead (Pb) is a heavy metal that induces the formation of free radicals and causes hepatocellular damage, making the liver one of the primary target organs of lead toxicity. Moringa oleifera leaves contain natural antioxidants with the potential to counteract oxidative stress induced by lead exposure. This study aimed to evaluate the effect of Moringa oleifera leaf simplicia on liver histopathology in white rats (Rattus norvegicus) exposed to lead acetate. A total of 20 rats were randomly divided into four groups: P0 (negative control; standard feed and water), P1 (positive control; 0.5 mg/head/day of lead acetate for 3 days), P2 (0.5 mg/head/day of lead acetate plus 0.1 g/mL/day of Moringa oleifera leaf simplicia), and P3 (0.5 mg/head/day of lead acetate plus 0.6 g/mL/day of Moringa oleifera leaf simplicia). Treatments were administered for 14 days via intragastric gavage. On day 15, the rats were euthanized, and liver tissues were collected, processed histologically, and stained with hematoxylin-eosin. Histopathological lesions, including congestion, fatty degeneration, and necrosis, were scored on a scale from 0 to 3 based on severity. The Kruskal-Wallis test showed significant differences among groups for all lesions (P < 0.05). The Mann-Whitney test revealed significant differences in hepatic congestion between P0 and P1, P0 and P2, as well as between P3 and P1-P2, while no significant difference was observed between P0 and P3. For fatty degeneration and necrosis, P0 differed significantly from P1, P2, and P3. In conclusion, Moringa oleifera leaf simplicia at a dose of 0.6 g/mL/day reduced the severity of hepatic congestion caused by lead exposure; however, its effects on fatty degeneration and necrosis were not statistically significant.